Effectiveness of warning graphic labels on cigarette packs in enhancing late-teenagers' perceived fear of smoking-related harms in Bangkok, Thailand - Surapong Chudech; Piyapong Janmaimool (SAGE Publishing, 2021)
Background: This study investigated the level of fear of smoking-related harms for teenagers of different gender, different levels of smoking behaviour, and difference in smoking levels of friends and family members, as influenced by warning graphic images on cigarette packs. The study also compared levels of this fear in categories based on participants' perception (e.g., scarier or less scary images). Design and Methods: The sample group was 353 undergraduate students at King Mongkut's University of Technology Thonburi in Bangkok, Thailand. Questionnaires containing 21 warning graphic images, aimed at measuring levels of fear of smoking-related harms, were conducted. Both descriptive statistics and inferential statistics, such as independent and dependent t-test, were used to analyse the data. Results: The results showed that warning graphic images exhibiting patients suffering from cancers (e.g., lung cancer or laryngeal cancer) and images of damaged body parts were perceived as the scariest warning images. In contrast, images that did not illustrate serious disease suffered by smokers were perceived as the least scary images. The scariest images generated a significant higher level of fear of smoking-related harms than the least scary images. In addition, non-smoking participants were more sensitive to scary warning images than smoking participants. It was also found that the level of fear of smoking-related harms was significantly based on individual cognitive judgment, and it was not affected by the influence of social groups such as friends and family members. Conclusions: Developing effective warning graphic images could directly contribute to individuals' perceived health risks and danger associated with smoking.